Global development finance 2001 : building coalitions for effective development finance (The World Bank, 2001)
Tracks the annual movement of international capital flows to developing countries and discusses selected analytical and policy issues in international finance for developing countries. Provides a review of developing countries' external debt and financial flows as well as consolidated statistics for all developing countries.